THE EFFECT OF OWNERS’ PERCEPTIONS AND BUSINESS OWNERS’ ACCOUNTING UNDERSTANDING ON THE USE OF ACCOUNTING INFORMATION(A Survey of Coffee Shop Businesses in Denpasar City) - Putu Ayu Agung Indira Putri; Made Yenni Latrini; Ni Luh Sari Widhiyani; Ni Nyoman Sri Rahayu Trisna Dewi (Adisam Publisher, 2026)
The rapid growth of coffee shop businesses in Denpasar City requires business owners to manage their businesses effectively through the use of accounting information. However, this development has not been fully accompanied by the optimal utilization of accounting information by business owners in making business decisions. This study aims to examine the effect of owners’ perceptions and business owners’ accounting understanding on the use of accounting information in coffee shop businesses in Denpasar City. This study employed a quantitative approach using primary data collected through questionnaires distributed to 103 coffee shop owners in Denpasar City selected using a purposive sampling technique. The data were analyzed using multiple linear regression analysis with the assistance of the Statistical Package for the Social Sciences (SPSS). The results indicate that owners’ perceptions and accounting understanding have a positive and significant effect on the use of accounting information in coffee shop businesses in Denpasar City. These findings demonstrate that owners’ positive perceptions of the importance of accounting information and a sound understanding of accounting can encourage business owners to utilize accounting information in business management and decision-making. Therefore, coffee shop owners in Denpasar City need to enhance their perceptions of the importance of accounting and their understanding of accounting processes so that accounting information can be optimally utilized to support business sustainability and development.